The Monetary Exchange Rate Model as a Long-Run Phenomenon - Jan J.J. Groen (Tinbergen Institute, 1998)
Pure time series-based tests fail to find empirical support formonetary exchange rate models. In this paper we apply pooled timeseries estimation on a forward-looking monetary model, resulting inparameter estimates which are in compliance with the underlyingtheory. Based on a panel version of the Engle and Granger (1987) two-stepprocedure we find that the residuals of our pooled estimated modelare stationary. This indicates that on a pooled time series levelthere is cointegration between the exchange rate and themacroeconomic fundamentals of this monetary model.
Keywords: 330; Wechselkurs; Zeitreihenanalyse; Theorie